The Rise and Progress of the West in the 15th-16th Centuries and its relationship with the Islamic world: KEBANGKITAN DAN KEMAJUAN BARAT PADA ABAD KE 15-16 M SERTA HUBUNGANNYA DENGAN DUNIA ISLAM - Ridwan; Ading Kusdiana; Wawan Hernawan (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This paper aims to explain the rise and progress of the West in the 15th-16th centuries and its relationship with the Islamic world. This writing uses historical research methods consisting of Heuristics, Criticism, Interpretation, and Historiography. The results of the writing provide an explanation that the Islamic world is a world that is able to bring changes to its social society, from rigidity of thought to openness in thinking because reason is given a special place, so that the Islamic world is able to create a very advanced civilisation in its time. Wherever the power of Islam stood then in that place also spread an advanced civilisation, such as in Baghdad, Egypt, and Spain which then spread to European countries. Europe, which had experienced a dark period of civilisation, turned into a nation of thinkers without having to be intimidated by the doctrines of the Church in power at that time, with the spirit to change and progress, they were able to bring European darkness to the rise and light of Europe, and all of this was none other than the contribution of Islamic civilisation that had taken a foothold in European countries in the past which made the opportunity to study science in the Islamic world.